MI Muhammadiyah Karanganyar sebagai Representasi Sekolah Unggulan di Karanganyar - Setyariza, Nur Ayu; Kusumawardani, Intan; Widayati, Sri Erna; Handayani, Yekti; Khoir, Mulyanto Abdullah (TSAQOFAH, 2024)
Excellent Schools can be defined as schools that are developed to achieve excellence resulting from the education provided. This means that superior schools are developed and processed like other conventional schools that have developed so far by providing additional treatment to all students. The school's excellence lies in how the school designs the school as an organization. The school's excellence lies in how the school designs the school as an organization. What this means is how the organizational structure of the school is structured, how the school community participates, how each person has appropriate roles and responsibilities and how the delegation and delegation of authority occurs accompanied by responsibility. The presence of Madrasah Ibtidaiyah Muhammadiyah (MIM) Karanganyar has given a positive image to the development of Islamic education in Karanganyar Regency. Even without the additional label of a Superior School or something similar, this madrasah has been able to show its image as an Islamic educational institution that prioritizes.